The investigation of sodium nitrite effects on the toxicokinetics of cyanide and thiocyanate - Sadettin Tanyıldızı; İbrahim Pirinçci; Sezai Kaya; Emine Baydan (Eurasian Journal of Veterinary Sciences)
This study was carried out to determine the effects of sodium nitrites on some toxicoklnetic parameters of cyanide and thiocyanate in sheep experimentally poisoned with amygdalin In this study, 18 sheep 50 — 60 kg weights were used. Amygdalin and sodium nitrite were given and the cyanide and thiocyanate levels in samples were determined Then some toxicokinetic parameters of the cyanide and thiocyanate in the blood samples taken at 0.5, 1, 2, 4, 8, 24, 48 and 72th hours were established. The sodium nitrite was given intravenously in doses 5 and 25 mg/kg and then the distribution half-lives of blood cyanide levels according to doses were respectively, 0.23±0.01 and 3.14±1.65 hours; the elimination half-lives were respectively, 60.80±13.41 and 126±24.33 hours; mean residence times were respectively, 88±10.04 and 185±2S.21 hours; the duration of maximal concentration were respectively, 48th hour; the maximal blood levels were respectively, 0.151 and 0148 µg/ml were determined. Besides, area under the curve values were according to doses were respectively, 11.28±1.24 and 9±S.62 µg.hour/ml; volume of distribution at steady state were respectively, 0.03±0.001 and 0.2±0.03 L/kg; clearance values were respectively, 0.44+0.12 and 0.16±0.09 ml/hour.kg were calculated. The distribution half-lives of blood thiocyanate levels according to doses were respectively, 18.30±2.21 and 29.44±3.41 hours; the elimination half-lives were respectively, 224.43±11.40 and 42.89±8.85 hours; mean residence times were respectively, 137.36±24.2 and 64.38±6.6S hours; the duration of maximal concentration were respectively, 24 and 48th hours; the maximal blood levels were respectively, 0.026 and 0.028 µg/ml were detennined. Besides, area under the curve values according to doses were respectively, 4.66±0.21 and 9.82±0.8 µg.hour/ml; volume of distribution at steady state were respectively, 0.147±0.03 and 0.162±0.03 L/kg; clearance values were respectively, 1.07+0.31 and 7.72±2.84 ml/hour.kg were established..